Los cuentos de Hadas en la Animación a la lectura de los niños de cuatro años del Centro Infantil Buen Vivir “Abdón Calderón” parroquia San Andrés, cantón Guano, Provincia de Chimborazo, período 2014-2015 - Cayambe Lema, Silvia Inés (2016)
The research topic is important because we want to learn more about how fairy tales help in encouraging reading in children of four years old, it had the cooperation of the teachers and authorities Children's Center to take the investigation. Because once certain variables could conduct surveys of teachers and children by observation sheet, which concluded that fairy tales encourages children of four years old because they are fun, interesting, intriguing. Furthermore an educational guide with activities that help teachers Children's Center to improve reading through stories was developed. It is important that teachers apply because children show great interest at the time of listening to stories that parents do the same at home as they would be to assist to the development of children, along with an interest in the stories w here they are promoting good reading habits